2003
DOI: 10.1001/archopht.121.12.1716
|View full text |Cite
|
Sign up to set email alerts
|

Ocular-Hypertensive and Anti-inflammatory Response to Rimexolone Therapy in Children

Abstract: Objective: To compare the ocular-hypertensive and antiinflammatory response to rimexolone (116-hydroxy-16␣fluoro-6␣methylpresdnisolone) and fluorometholone (21-deoxy-9␣fluoro-6␣methylprednisolone) therapy in children's eyes.Methods: With parental consent, children who underwent surgical procedures for bilateral symmetric strabismus from January 18, 2000, through November 16, 2001, were recruited. One eye was randomized to receive topical 1% rimexolone while the contralateral eye received topical 0.1% fluoromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…After 4-6 weeks, the patient can be switched to less effective drugs (hence, drugs causing fewer adverse effects: e.g., rimexolone) [35,45,46] (IA). In individual cases, the lesser efficacy of the anti-inflammatory preparations needs to be weighed against the problems associated with more frequent application and compliance.…”
Section: Treatment Of Chronic or Chronic Recurring Uveitismentioning
confidence: 99%
See 1 more Smart Citation
“…After 4-6 weeks, the patient can be switched to less effective drugs (hence, drugs causing fewer adverse effects: e.g., rimexolone) [35,45,46] (IA). In individual cases, the lesser efficacy of the anti-inflammatory preparations needs to be weighed against the problems associated with more frequent application and compliance.…”
Section: Treatment Of Chronic or Chronic Recurring Uveitismentioning
confidence: 99%
“…Rimexolone may be effective in cases of steroid-induced ocular hypertension, but compared to prednisolone acetate 1% and dexamethasone 0.1%, it shows a lower antiinflammatory effect [35,45] (IA). Table 8 Evidence-based, interdisciplinary guidelines for anti-inflammatory treatment of uveitis associated with juvenile idiopathic arthritis (Key statements)…”
Section: Treatment Of Chronic or Chronic Recurring Uveitismentioning
confidence: 99%
“…In two other studies, one reported that rimexolone was as effective as prednisolone after phacoemulsification surgery and the other reported that both have the same efficacy in controlling inflammation in patients with anterior uveitis [16]. Fan et al reported that the ocular pressure-increasing effect of rimexolone is much more prominent in children with postoperative inflammation than in adult patients [13]. The period of our study was not long enough to evaluate the pressure-increasing effect of both medications.…”
Section: Discussionmentioning
confidence: 68%
“…This is particularly true for steroids that have a predilection for elevating IOP. Corticosteroids, on the other hand, reduce short term complications such as high intra-ocular pressure, photophobia, pain, and low visual acuity [2,10,[12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Fluoromethalone alcohol 0.1% causes an IOP elevation between 2.6 and 5.8 mmHg, with the peak IOP being between 17.1 and 20.6 mmHg after a mean duration of 6-15 days in children [30][31][32]. Its IOP-elevating potential is also low in adults who are known to be steroid responders and comparable to that of rimexolone 1.0% [33].…”
Section: Reviewmentioning
confidence: 96%